Governing Banks: A British Perspective - Andy Milllneux (The International Journal of Banking and Finance, 2011)
This conceptual paper considers the corporate governance of shareholder owned deposit taking banks in light of the Global Financial Crisis (GFC). Deposit taking banks present a special corporate governance problem because depositors (and taxpayers) are stakeholders. The GFC revealed significant weaknesses in the regulation and corporate governance of banks. The UK government commissioned the Walker Review of the corporate governance of UK banks in February 2009. Its recommendations are discussed in the context of the wider governance (including regulation) of banks. Regulation and corporate governance systems should focus on the establishment of effective internal risk control mechanisms and the good management of banks.